Encapsulating perovskite solar cells to withstand damp heat and thermal cycling1. Issue 2 (10th July 2018) - Cheacharoen, Rongrong; Boyd, Caleb C.; Burkhard, George F.; Leijtens, Tomas; Raiford, James A.; Bush, Kevin A.; Bent, Stacey F.; McGehee, Michael D.
Abstract : Glass and edge seal encapsulation of a perovskite solar cell to enable stability through damp heat and thermal cycling tests. Abstract : Perovskite solar cells (PSCs) are highly promising, but they are mechanically fragile, composed of layers with mismatches in thermal expansion coefficients, and known to decompose in the presence of heat and moisture. Here we show the development of a glass–glass encapsulation methodology for PSCs that enables them to pass the industry standard IEC 61646 damp heat and thermal cycling tests. It is important to select a thermally stable perovskite composition to withstand the encapsulation process at 150 °C and design a cell that minimizes metal diffusion. Moreover, the package needs an edge seal to effectively prevent moisture ingress and an inert encapsulant with an appropriate elastic modulus to hold the package together while allowing for compliance during temperature fluctuations. Our work demonstrates that industrially relevant encapsulation techniques have the potential to enable the commercial viability of PSCs.